The role of bandwagon effect and FoMo in viral marketing - Rizqah Rizqah; Syaakir Sofyan; Noval Noval; Sofyan Bachmid; Hamka Hamka (Journal of Innovation in Business and Economics, 2025)
The digitalization era has significantly reshaped consumer behavior, especially among Generation Z, whose purchasing decisions are increasingly influenced by non-price factors such as social trends and peer dynamics. This study examines the direct and moderating effects of the bandwagon effect and Fear of Missing Out (FoMO) on consumptive buying behavior, with viral marketing as a mediating factor, in the context of Palu, Indonesia. Adopting a quantitative explanatory approach, data were collected from 398 respondents aged 18–26 through structured online surveys and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that both the bandwagon effect and FoMO significantly and positively impact consumptive buying behavior, with FoMO demonstrating a stronger influence. Contrary to expectations, neither variable moderates the relationship between viral marketing and consumptive behavior. Moreover, viral marketing exhibits a significant negative effect, potentially due to perceptions of intrusiveness or oversaturation. These findings suggest that marketing strategies should emphasize social validation, exclusivity, and scarcity-based promotions to effectively engage Generation Z consumers.